General practitioner and nurse practitioner attitudes towards electronic reminders in primary care: a qualitative analysis. Issue 7 (12th July 2021) - Cecil, Elizabeth; Dewa, Lindsay Helen; Ma, Richard; Majeed, Azeem; Aylin, Paul
Abstract : Objectives: Reminders in primary care administrative systems aim to help clinicians provide evidence-based care, prescribe safely and save money. However, increased use of reminders can lead to alert fatigue. Our study aimed to assess general practitioners' (GPs) and nurse practitioners' (NPs) views on electronic reminders in primary care. Design: A qualitative analysis using semistructured interviews. Setting and participants: Fifteen GPs and NP based in general practices located in North-West London and Yorkshire, England. Methods: We collected data on participants' views on: (1) perceptions of the value of information provided; (2) reminder-related behaviours and (3) how to improve reminders. We carried out a thematic analysis. Results: Participants were familiar with reminders in their clinical systems and felt many were important to support their clinical work. However, participants reported, on average, 70% of reminders were ignored. Four major themes emerged: (1) reaction to a reminder, which was mixed and varied by situation. (2) Factors influencing the decision to act on reminders, often related to experience, consultation styles and interests of participants. Time constraints, alert design, inappropriate presentation and litigation were also factors. (3) Negative consequences of using reminders were increased workload or costs and compromising GP and NPs behaviour. (4) Factors relating to improving users' engagement with reminders were prevention of unnecessary reminders through data linkage across healthcare administrative systems or the development of more intelligent algorithms. Participants felt training was vital to effectively manage reminders. Conclusions: GPs and NPs believe reminders are useful in supporting the provision of good quality patient care. Improving GPs and NPs' engagement with reminders centres on further developing their relevance to their clinical practice, which is personalised, considers cognitive workflow and suppresses inappropriate presentation.